Food supplements from a Grasshopper: A developmental stage-wise evaluation of amino acid profile, protein and vitamins in Brachystola magna (Girard) - Zamudio-Flores, P.B.; -Gonzaléz, M. Hernández; Cano, V.G. García- (Emirates Journal of Food and Agriculture, 2019)
Insects can be used as an easily accessible food supplement; however, for nutritional purposes it is necessary to consider its protein content, amino acids composition and vitamin content. In this study a nutritional characterization (protein content, amino acid profile and hydrosoluble and liposoluble vitamins) was performed to the Brachystola magna (Girard) grasshopper in four stages of its biological cycle (egg, nymph 3, nymph 4 and adult). In the adult stage the highest values of protein content (> 59%) were observed compared with the other stages of development. At all stages of B. magna the presence of 9 out of the 10 essential amino acids were detected (just tryptophan amino acid was absent). Significant increases in the fat-soluble vitamins (A, D and E) were observed as the stage of development of B. magna increased, with the increase of vitamin E of ≈ 662% in the adult stage; however, the water-soluble vitamins of the B complex remained constant at all stages, but vitamin C, which increased significantly in the adult stage of this insect cycle. Results suggest that Brachystola magna (Girard) could be a potential source of consumption for people with specific health needs.